From church to museum and back again. The de-sacralization and re-sacralization of Kinnarumma's old wooden church - Andersson, Erik J (Approaching Religion, 2023)
In the small village of Kinnarumma in western Sweden an old wooden church was replaced by a new church buildning in the early twentieth century. The old church was de-sacralized by being moved to an open-air museum in Borås and used there for exhibitions and the storage of museum objects. The need for more church premises in the city led to the re-sacralization of the old church in 1930. The transition of Kinnarumma’s old wooden church to museum object, its museumification, was an expression of change in religious heritage, and its re-sacralization expressed an unchanged part of the same heritage.
Keywords: religious heritage; Church history; wooden churches in Sweden; desacralization; resacralization